Test Of Flavonoid Activity of Durian (Durio Zibethinus) Seeds and Skins as Natural Insecticides in Controlling Mealybug (Pseudococcidae) - Maharani, Lila; Zuhro, Fatimatuz; Mahbubah, Fina Saffanatul (BIOEDUKASI, 2024)
Several references indicate that active metabolites found in natural plant resources such as flavonoids and saponins have the potential as natural insecticides. One of natural plant resource that has the potential as a natural insecticide is durian, because in durian albedo there are flavonoids and saponins. In addition, durian seeds also contain flavonoids of 29.74 μg / mL. Based on this background, the author took the initiative to test the activity of flavonoid content in durian seed extract and albedo to determine its effectiveness as a natural insecticide for mealybug pest control. This research consists of 2 stages, including; extraction of flavonoids from durian seeds and albedo (peels), and testing of flavonoid activity of durian seed and peels extracts against mealybug mortality. Extraction of flavonoids from durian seeds and peels using socletation method and spectrophotometry tested. The results of flavonoid and phenolic analysis of durian seed extract are higher than durian albedo extract. The effectiveness test was carried out on the population of mealybug pests that had been acclimatized for 24 hours, placed on cocoa peels media that had been soaked in the treatment solution for 15 minutes, then the mortality rate was observed. The treatment given was albedo extract 12.5 g/100ml; albedo extract 25 g/100 ml; durian seed extract 12.5 g/100 ml; 25 g/100ml; albedo and seed extract 12.5 g/100 ml; albedo and seed extract 25 g/100 ml; positive control and negative control. The test results showed that the mortality of mealybugs in the treatment of seed extract 12.5 g /100 ml was not significantly different from the positive control treatment, this showed that durian seed extract 12.5 g / 100ml is expected to replace the use of chemical insecticides in the control of mealybug pests.